Expanding the toolbox for HIV-1 protease inhibitor resistance assessment and drug discovery targeting protease precursor autoprocessing - Jeep, Ryan, author; Chen, Chaoping, advisor; Stasevich, Tim, committee member; Schauer, Grant, committee member; Quackenbush, Sandra, committee member (Colorado State University. Libraries, 2025)
HIV-1 protease (PR) is initially synthesized as part of the Gag-Pol polyprotein precursor. Regulated protease precursor autoprocessing liberates the mature PR, which is required for viral infectivity. Thus, mature PR is the primary target of nine FDA-approved protease inhibitors (PIs). Numerous resistance-associated mutations (RAMs) within and beyond the PR gene have been identified which undermine the efficacy and prognosis of combination antiretroviral therapy (cART). The precise relationship between PR genotype, phenotype, and clinical treatment outcome is still not fully understood, and thus resistance to HIV-1 protease inhibitors (PI) remains a persistent challenge. Using a variety of mammalian cell-based assays, including a newly developed infectivity assay capable of detecting single infectious units, we investigated a PR double mutant, V77I/V82T, identified in a patient resistant to indinavir (IDV). These assays revealed notable variations in PI susceptibility, implicating the context-dependent catalytic flexibility of HIV-1 mature PR and its precursors in resistance development. Our infectivity assay accurately replicated the clinically observed IDV resistance mediated by the V77I/V82T mutant and delineated the roles of individual mutations, demonstrating that while V82T confers resistance to IDV, it also increases sensitivity to darunavir (DRV). These findings add to the mounting evidence that precursor PRs are less sensitive to PI than mature PRs and define our lab's infectivity assay as a powerful tool for sensitive evaluation of drug effectiveness and resistance. We also evaluated PI response of a panel of prototypical multi-PI-resistant mutants. Our comparative analyses demonstrated that our infectivity assay performed comparably to the conventional PhenoSense® assay in assessing drug resistance. Our results confirmed that the tested mutants exhibited diverse and distinct response profiles to darunavir (DRV), lopinavir (LPV), atazanavir (ATV), and saquinavir (SQV). Notably, our analysis revealed that high levels of resistance to LPV and ATV develop more easily than resistance to DRV and SQV suggesting that different RAM combinations result in distinct resistance profiles in these strains (see Chapter 3). Our infectivity assay provided improved resolution on PI susceptibility by correlating drug responses with PI concentrations and thus may aid in optimizing treatment regimens for people living with HIV experiencing drug resistance. To explore alternative therapeutic strategies, we developed a cell-based high-throughput screening (HTS) platform targeting precursor autoprocessing and screened approximately 320,000 small molecules and 2,000 natural product extracts (NPEs). We identified 27 small molecules and 20 NPEs that partially suppress precursor autoprocessing. A highly sensitive infectivity assay confirmed that several small molecules inhibited viral infectivity in a dose-dependent manner, with EC50 values in the low micromolar range. Notably, small molecule C7 exhibited comparable potency against both wild-type and drug-resistant HIV strains, suggesting a novel mechanism of action. Two crude NPEs showed dose-dependent inhibitory activity in live virus and preliminary fractionation of the crude extracts partially separated inhibitory from non-inhibitory compounds. This study provides proof of concept for an innovative drug discovery approach targeting HIV-1 PR autoprocessing as a potential strategy to combat drug resistance.
Keywords: drug discovery; infectivity; autoprocessing; small molecule; HIV